(3GdeNJUQ ef GdeRfis - (3GdeRfj GdTGaYj,J (B264 (3g` s
(3ChdgG (B:s
(3jHOC HcJGH GdWgGQI s
(3BNQgG (B:s
(3jfJgi HcJGH GdeOQ LOjO hbOje s
(3HChdg agQS HNW MOjK LOkGs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1635s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3Gdabg GdTGaYjs